Pusat dan Periphery: Pengaruh Pendapatan Daerah, Belanja Modal, Belanja Pegawai terhadap Akuntabilitas Pelaporan Keuangan Pemerintah Daerah Kabupaten/Kota Di Provinsi Sumatera Selatan - Adelia Putri Yulna; Nelly Masnila; Sri Hartaty (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of the study was to test and analyze the effect of local revenue, capital expenditure, employee expenditure on the accountability of financial reporting of district/ city local governments in South Sumatra Province during the period 2013-2022. The data used in this study are secondary data with a research sample of 15 regencies / cities in South Sumatra Province. This study uses quantitative analysis techniques with panel data regression analysis tools. The results of this study (1) Regional income, capital expenditure and employee expenditure have a positive and significant effect on the Accountability of Regional Financial Statements (2) Regional income, capital expenditure and employee expenditure simultaneously affect the Accountability of Regional Financial Statements. Keywords: Regional Revenue, Capital Expenditure, Employee Expenditure